Three-Dimensional Printing of Fetal Models of Congenital Heart Disease Derived From Microfocus Computed Tomography: A Case Series - Sandrini, Camilla; Lombardi, Claudio; Shearn, Andrew I. U.; Ordonez, Maria Victoria; Caputo, Massimo; Presti, Francesca; Luciani, Giovanni Battista; Rossetti, Lucia; Biglino, Giovanni (Frontiers in Pediatrics, 2020)
This article presents a case series of n=21 models of fetal cardiovascular anatomies obtained from post mortem microfocus computed tomography (micro-CT) data. The case series includes a broad range of diagnoses (e.g. tetralogy of Fallot, hypoplastic left heart syndrome, dextrocardia, double outlet right ventricle, atrio-ventricular septal defect) and cases also had a range of associated extra-cardiac malformations (e.g. VACTERL syndrome, central nervous system anomalies, renal anomalies). All cases were successfully reconstructed from the microfocus computed tomography data, demonstrating the feasibility of the technique and of the protocols, including in-house printing with a desktop 3D printer (Form2, Formlabs). All models were printed in 1:1 scale as well as with the 5-fold magnification, to provide insight into the intra-cardiac structures. Possible uses of the models include education and training.